Pengaturan Hukum Terhadap Pelaku yang Menghalangi Proses Peradilan (Obstruction of Justice) Dikaji Dari Perspektif Hukum Pidana dan Kepastian Hukum - Jalil, M.Abdul (Jurnal Global Ilmiah, 2025)
The criminal justice process is an essential instrument in realizing the rule of law, which emphasizes justice, legal certainty, and utility. In practice, however, the phenomenon of obstructing the course of justice, commonly referred to as obstruction of justice, frequently occurs. Such acts may include concealing, destroying, or falsifying evidence; influencing, pressuring, or intimidating witnesses; as well as obstructing the investigation, prosecution, or trial proceedings. This phenomenon poses a serious threat because it undermines the integrity of the justice system, weakens law enforcement efforts, and ultimately disrupts legal certainty, which is one of the primary objectives of criminal law. This study aims to analyze the legal regulation of perpetrators of obstruction of justice within the Indonesian legal system and to examine how such regulation is viewed from the perspective of criminal law and the principle of legal certainty. The research method employed is normative legal research, using a statute approach and a conceptual approach. Primary legal materials include the Indonesian Penal Code (KUHP), the Code of Criminal Procedure (KUHAP), and other relevant legislation that specifically regulates obstruction of justice, such as the Anti-Corruption Law, the Corruption Eradication Commission Law, and the Anti-Money Laundering Law. The findings of this study indicate that the regulation of obstruction of justice in Indonesia remains partial, fragmented, and has yet to be comprehensively formulated within the Penal Code or the Code of Criminal Procedure. This condition creates difficulties in practice, particularly when obstruction of justice is committed outside the scope of special criminal laws that explicitly address it. From the perspective of criminal law, this opens the possibility of multiple interpretations in determining punishable acts, thereby reducing the effectiveness of law enforcement. From the perspective of legal certainty, the absence of clear and codified regulation leads to disparities in court decisions, inconsistency in law application, and a weakening of legal protection guarantees for society. This research underscores the urgency of reforming Indonesia’s criminal law through systematic codification of obstruction of justice as a distinct criminal offense. The Draft Penal Code (RKUHP) should explicitly regulate obstruction of justice with clear, detailed, and comprehensive provisions in order to ensure legal certainty, strengthen the integrity of the justice system, and uphold the rule of law.